2019
DOI: 10.1111/obr.12866
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of obesity, with a dietary component, and eating disorder risk in children and adolescents: A systematic review with meta‐analysis

Abstract: Summary This review aimed to investigate the impact of obesity treatment, with a dietary component, on eating disorder (ED) prevalence, ED risk, and related symptoms in children and adolescents with overweight or obesity. Four databases were searched to identify pediatric obesity treatment interventions, with a dietary component, and validated pre‐post intervention assessment of related outcomes. Of 3078 articles screened, 36 met inclusion criteria, with a combined sample of 2589 participants aged 7.8 to 16.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
121
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(126 citation statements)
references
References 88 publications
(754 reference statements)
3
121
1
1
Order By: Relevance
“…This review, in combination with findings from two other reviews conducted by our team, demonstrates that treatment interventions for children and adolescents with obesity lead to improvements across the spectrum of psychological wellbeing in the short to medium term, including self-esteem and body image (current review), depression and anxiety (26/64 overlapping studies), 124 and eating disorders and eating disorder risk (16/64 overlapping studies) 125 following intervention. Reduced selfesteem and poor body image have a role in perpetuating further psychological pathology.…”
Section: Discussionmentioning
confidence: 74%
“…This review, in combination with findings from two other reviews conducted by our team, demonstrates that treatment interventions for children and adolescents with obesity lead to improvements across the spectrum of psychological wellbeing in the short to medium term, including self-esteem and body image (current review), depression and anxiety (26/64 overlapping studies), 124 and eating disorders and eating disorder risk (16/64 overlapping studies) 125 following intervention. Reduced selfesteem and poor body image have a role in perpetuating further psychological pathology.…”
Section: Discussionmentioning
confidence: 74%
“…Parents and clinicians have been concerned of inducing eating disorders later in childhood if the weight of the child is addressed to early 35 . However, this has not been corroborated 36 . Thus, in clinical practice, it has been discussed among paediatricians at what age overweight/obesity should be addressed as an issue when advising parents at the Child Health Centers.…”
Section: Discussionmentioning
confidence: 99%
“…Others support the idea that new treatments are needed to address ED pathology and weight loss concurrently [ 40 ]. A recent systematic review and meta-analysis found that structured and professionally run obesity treatments are associated with reduced ED prevalence, risk, and symptoms in children [ 41 ]. However, because clinicians who work with patients with EDs often discover that the onset of disordered eating follows the first attempt to diet, many prefer a “do no harm” approach.…”
Section: Introductionmentioning
confidence: 99%